Curriculum Modernization Strategy in Salaf Islamic Boarding School Based on Indonesian National Qualification Framework - Catur Ratmoko Alid; Pardiman Pardiman; Ridwan Basalamah (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article reveals the strategy of modernizing the curriculum of the Raudhatul Ulum Islamic Boarding School Jember based on the Indonesian national qualifications framework. With their salaf characteristics, Islamic boarding schools continue to innovate continuously in adapting the curriculum. This type of research is qualitative with a case study approach, data obtained from interviews, observations and documentation, then analyzed by condensing, displaying data and drawing conclusions. The findings of the study indicate that based on the results of the study, it can be concluded that first, pesantren remain consistent in exclusively studying classical books with a class system like modern schools, except that the subject matter of the study remains in the field of religion. Second, Islamic boarding schools incorporate the national curriculum into the cottage learning system so that the practice of teaching religion and science is realized in a balanced class form. Third, pesantren is consistent in traditional spending to study the yellow books and provide opportunities for santri to gain education provided by pesantren, which has been adapted to the Indonesian national qualification framework.